Prévalence de la fibrillation atriale non valvulaire et de l´accident vasculaire cérébral ischémique et facteurs associés à la fibrillation atriale non valvulaire chez les patients hypertendus: étude observationnelle à propos de 2887 patients - Bahloul, Amine (Pan Afr Med J, 2021)
INTRODUCTION: high blood pressure (HBP), atrial fibrillation (AF) and ischemic stroke are three public health problems. The purpose of this study was to determine the prevalence of AF and ischemic stroke in hypertensive patients and the factors associated with the occurrence of non-valvular AF in these patients. METHODS: we used data collected in the Department of Cardiology at the University Hospital of Sfax as a part of National Tunisian Registry of Hypertension. We examined the associations between different socio-demographic, clinical, paraclinical, and therapeutic variables and AF in hypertensive patients using logistic regression models. RESULTS: our sample consisted of 2887 patients with a sex ratio of 0.95. The average age of patients was 65 years (±11). AF was found in 230 patients (8%), while ischemic stroke was found in 152 patients (5.3%). Multivariate analysis highlighted that independent factors associated with an increase in the prevalence of AF were: advanced age (p = 0,001, Odds Ratio (OR) = 1,647, 95% confidence interval ( CI): 1,1227-2,213), the detection of left ventricular hypertrophy (LVH) on cardiac ultrasound (p= 0,004, OR= 2,140, 5%CI 9: 1,281-3,576), and left ventricular ejection fraction (LVEF) < 50% (p<0,001, OR=4,677, 95% CI: 2,715 and 8.057). CONCLUSION: this study confirms that there is a direct and independent relationship between high blood pressure, advanced age, LVH and AF. AF in patients with high blood pressure is a disease progression leading to an increased risk of ischemic stroke. Optimal high blood pressure control is a priority in hypertensive patients, especially in the elderly, aiming at preventing the risk of AF and ischemic stroke.